Porous metal structure and preparation method thereof
By recrystallization annealing, phase separation heat treatment and reduction annealing treatment on the cold-rolled alloy foil, a porous metal structure with good strength and toughness is prepared, which solves the problem that the porous metal structure is prone to grain boundary corrosion cracks during the preparation process.
Patent Information
- Application Number
- CN202311849942.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-07
- Filing Date
- 2023-12-29
- Publication Date
- 2025-05-09
AI Technical Summary
The existing porous metal structures are prone to grain boundary corrosion cracks during the preparation process, which affects their performance and application.
By recrystallization annealing, phase separation heat treatment and reduction annealing treatment on the cold-rolled alloy foil, a porous metal structure with good strength and toughness was prepared. The specific steps include: rapid cooling after recrystallization annealing, then phase separation heat treatment to precipitate the second component phase, and reduction annealing treatment under a reduction atmosphere to repair grain boundary corrosion cracks.
This method can partially or even completely repair grain boundary corrosion cracks formed by dealloyment treatment, improve the strength and toughness of porous metal structures, and enhance its performance in applications such as batteries.
Smart Images

Figure CN119956359A_ABST
Abstract
Description
[0001] This application claims priority to Chinese patent application 202311469631.3, filed on November 7, 2023, entitled “Porous Metal Structure and Preparation Method Thereof”, the entire contents of which are incorporated herein by reference. Technical Field
[0002] The present application relates to a porous metal structure and a preparation method thereof. Background Art
[0003] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in consumer electronics, power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. The negative electrode is an important component of the battery, which will affect the performance of the battery. At present, the negative electrode of the battery is usually formed by setting a negative electrode film layer including negative electrode active materials such as graphite on a copper foil. However, with the continuous expansion of battery application fields, people's demand for high energy density batteries is increasing. Metal batteries and negative electrode-free batteries do not use negative electrode film layers, so they can have high energy density, but the uneven deposition and dendrite problems of metals restrict the development of metal batteries and negative electrode-free batteries. As an important component of metal batteries and negative electrode-free batteries, the negative electrode current collector is expected to alleviate the uneven deposition and dendrite problems of metals by improving it.
[0004] Porous metal structures have the advantages of light weight and large specific surface area. When used in batteries, they can increase the energy density of the battery and improve the reliability of the battery. In particular, when the negative electrode of metal batteries and negative electrode-free batteries adopts porous metal structures, it can also reduce the uneven deposition of metals and dendrite problems.
[0005] Alloy forging and cold rolling are effective methods for mass production of alloy foils, and dealloying of cold-rolled alloy foils is an effective method for obtaining porous metal structures. Limited by the current production process of alloy foils and dealloying process, there are often many intergranular corrosion cracks inside the porous metal structures currently prepared, which will affect the performance of the porous metal structure and its practical application in batteries.
[0006] The above statements are only used to provide background information related to the present application and do not necessarily constitute prior art. Summary of the invention
[0007] The present application provides a porous metal structure and a preparation method thereof, which can partially or even completely repair intergranular corrosion cracks formed by dealloying treatment, and can also make the prepared porous metal structure have better strength and toughness.
[0008] In a first aspect, the present application provides a method for preparing a porous metal structure, comprising the following steps: providing a cold-rolled alloy foil; subjecting the alloy foil to a recrystallization annealing treatment, and then subjecting the alloy foil to a first cooling treatment to obtain an alloy foil having a first component phase; subjecting the alloy foil having the first component phase to a phase separation heat treatment, and then subjecting the alloy foil to a second cooling treatment to precipitate a second component phase and obtain an alloy foil having both a first component phase and a second component phase, wherein the temperature of the phase separation heat treatment is lower than the temperature of the recrystallization annealing treatment, and the average cooling rate of the second cooling treatment is lower than the average cooling rate of the first cooling treatment; subjecting the alloy foil having the first component phase and the second component phase to a dealloying treatment, and then subjecting the alloy foil to a reduction annealing treatment in a reducing gas atmosphere, and then subjecting the alloy foil to a third cooling treatment to obtain a porous metal structure.
[0009] The preparation method provided in the embodiment of the present application can partially or even completely repair the intergranular corrosion cracks formed by the dealloying treatment, and can also make the prepared porous metal structure have better strength and toughness.
[0010] In some embodiments, the average cooling rate of the first cooling treatment is greater than or equal to 100°C / min, and can be selected to be greater than or equal to 200°C / min. This is beneficial to reducing the element segregation problem at the grain boundary, and is also beneficial for the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing treatment, so that the grain boundary corrosion cracks can be better repaired, and the prepared porous metal structure can also have better toughness.
[0011] In some embodiments, the average cooling rate of the second cooling treatment is less than or equal to 2°C / min. This is beneficial to reducing the interphase stress between the first component phase and the second component phase in the phase-separated alloy, and is beneficial to the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing treatment, so that the grain boundary corrosion cracks can be better repaired, and the prepared porous metal structure can also have better toughness.
[0012] In some embodiments, the first cooling process is a water cooling process, which is beneficial to reducing the element segregation problem at the grain boundary and facilitating the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing process, thereby better repairing the grain boundary corrosion cracks and making the prepared porous metal structure have better toughness.
[0013] In some embodiments, the second cooling process is a furnace cooling process, which is beneficial to reducing the interphase stress between the first component phase and the second component phase in the phase-separated alloy, and is beneficial to the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing treatment, so that the grain boundary corrosion cracks can be better repaired, and the prepared porous metal structure can also have better toughness.
[0014] In some embodiments, the first temperature reduction treatment cools the alloy foil to below 50° C. This can reduce the risk of surface oxidation of the alloy foil.
[0015] In some embodiments, the second cooling treatment is performed to cool the temperature to below 50° C. This can reduce the risk of surface oxidation of the alloy foil.
[0016] In some embodiments, the recrystallization annealing process is performed in a muffle furnace.
[0017] In some embodiments, the phase separation heat treatment is performed in a tube furnace. Optionally, the heating rate of the tube furnace is 2°C / min-10°C / min, and optionally 5°C / min-10°C / min.
[0018] In some embodiments, the reducing gas of the reducing annealing process includes ammonia or a mixture of hydrogen and an inert gas.
[0019] In some embodiments, the flow rate of the reducing gas in the reduction annealing treatment is 100 SCCM-2000 SCCM.
[0020] In some embodiments, the reduction annealing treatment is performed in a tube furnace. Optionally, the heating rate of the tube furnace is 2°C / min-10°C / min, and optionally 5°C / min-10°C / min.
[0021] In some embodiments, the average cooling rate of the third cooling treatment is less than or equal to 2°C / min, and optionally, the third cooling treatment process is a furnace cooling process. The use of a slow cooling process can reduce the stress of the porous metal structure and make it less likely to curl.
[0022] In some embodiments, the third cooling treatment cools the temperature to below 50° C. This can reduce the risk of surface oxidation of the alloy foil.
[0023] In some embodiments, the alloy foil is a copper alloy foil, and the copper alloy foil includes a Cu element and a non-Cu metal element. The standard electrode potential of the non-Cu metal element is less than the standard electrode potential of the Cu element. Optionally, the non-Cu metal element includes one or more of Mn, Zn, Ni, Al, and Fe.
[0024] In some embodiments, the atomic content of the non-Cu metal element in the copper alloy foil is greater than 60 at.%, and may be 65 at.%-80 at.%.
[0025] In some embodiments, the first component phase includes a gamma phase.
[0026] In some embodiments, the second component phase includes an alpha phase.
[0027] In some embodiments, the temperature of the recrystallization annealing treatment is 720°C-850°C.
[0028] In some embodiments, the holding time at the recrystallization annealing temperature is 10 min-60 min.
[0029] By adjusting the temperature of the recrystallization annealing treatment and / or within the above range, it is beneficial to obtain an alloy foil having a first component phase with good plastic processing ability, and it is also beneficial to precipitate the second component phase during the phase separation heat treatment.
[0030] In some embodiments, the temperature of the phase separation heat treatment is 620°C-700°C.
[0031] In some embodiments, the holding time at the phase separation heat treatment temperature is 60 min-360 min.
[0032] By adjusting the temperature of the phase separation heat treatment and / or within the above range, it is beneficial to precipitate the second component phase during the phase separation heat treatment, and it is also beneficial to obtain a micron-level porous metal structure after the subsequent reduction annealing treatment.
[0033] In some embodiments, the reduction annealing treatment is performed at a temperature of 700°C-900°C, and optionally 720°C-900°C.
[0034] In some embodiments, the holding time at the reduction annealing temperature is 30 min-120 min.
[0035] By adjusting the temperature and / or time of the reduction annealing treatment within the above range, it is beneficial for the metal atoms to diffuse and move due to heat, so as to better repair the intergranular corrosion cracks formed by the dealloying treatment; it can also make the prepared porous metal structure self-supporting and avoid the problem of structural collapse; it can also make the prepared porous metal structure have better toughness.
[0036] In some embodiments, the process of dealloying the alloy foil having the first component phase and the second component phase comprises a free corrosion dealloying process and an electrochemical corrosion dealloying process.
[0037] In a second aspect, the present application provides a porous metal structure prepared by the preparation method of the first aspect of the present application.
[0038] Optionally, the porous metal structure is a porous copper structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A cross-sectional SEM image of the porous copper intermediate obtained by the dealloying treatment in Example 1 is shown.
[0040] Figure 2 The cross-sectional SEM image of the porous copper intermediate obtained by the dealloying treatment in Example 1 is shown, and the porous copper intermediate is subjected to plasma cutting and polishing treatment.
[0041] Figure 3 A cross-sectional SEM image of the porous copper structure prepared in Example 1 is shown.
[0042] Figure 4 A cross-sectional SEM image of the porous copper structure prepared in Example 2 is shown.
[0043] Figure 5 A cross-sectional SEM image of the porous copper structure prepared in Example 6 is shown.
[0044] Figure 6 A cross-sectional SEM image of the porous copper structure prepared in Example 7 is shown.
[0045] Figure 7 A cross-sectional SEM image of the porous copper intermediate obtained by dealloying treatment in Comparative Example 1 is shown.
[0046] Figure 8 A cross-sectional SEM image of the porous copper intermediate obtained by the dealloying treatment in Comparative Example 1 is shown, and the porous copper intermediate is subjected to plasma cutting and polishing treatment.
[0047] Fig. 9 A cross-sectional SEM image of the porous copper structure prepared in Comparative Example 1 is shown.
[0048] Fig.10 A cross-sectional SEM image of the porous copper structure prepared in Comparative Example 2 is shown.
[0049] Fig.11 A cross-sectional SEM image of the porous copper structure prepared in Comparative Example 5 is shown. DETAILED DESCRIPTION
[0050] Hereinafter, the porous metal structure of the present application and the method for preparing the same are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0051] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0052] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0053] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0054] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0055] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0056] In the description of the embodiments of the present application, unless otherwise specified, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Furthermore, a first feature being “above”, “above”, or “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, or “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0057] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.
[0058] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.
[0059] The embodiment of the present application provides a method for preparing a porous metal structure.
[0060] The preparation method comprises the following steps: providing a cold-rolled alloy foil; performing recrystallization annealing treatment on the alloy foil, and then performing a first cooling treatment to obtain an alloy foil having a first component phase; performing phase separation heat treatment on the alloy foil having the first component phase, and then performing a second cooling treatment to precipitate a second component phase and obtain an alloy foil having both the first component phase and the second component phase, wherein the temperature of the phase separation heat treatment is lower than the temperature of the recrystallization annealing treatment, and the average cooling rate of the second cooling treatment is lower than the average cooling rate of the first cooling treatment; performing dealloying treatment on the alloy foil having the first component phase and the second component phase, and then performing reduction annealing treatment in a reducing gas atmosphere, and then performing a third cooling treatment to obtain a porous metal structure.
[0061] Alloys are usually composed of relatively active metals and relatively inactive metals. Dealloying is the process of selectively dissolving the relatively active metals in the alloy to form pores.
[0062] The thickness of the alloy foil used to prepare the battery-grade porous metal structure is usually very small, for example, it is mostly at the micron level (for example, usually tens of microns to hundreds of microns). Therefore, the preparation process of the alloy foil usually requires multiple cold rolling. However, the alloy is prone to rolling orientation, element segregation, stress accumulation and other problems after repeated cold rolling and thinning, which will reduce the structural strength of the alloy foil. An alloy with good plastic processing ability can be obtained by performing recrystallization annealing on the alloy foil after cold rolling. However, when a porous metal structure with high porosity is prepared by de-alloying the alloy foil, the volume shrinkage of the alloy foil is serious, which causes the prepared porous metal structure to be unable to support itself, and it is very easy to produce intergranular corrosion cracks, thereby affecting the practical application of the porous metal structure.
[0063] The method for preparing a porous metal structure provided in the embodiment of the present application is divided into four stages: (1) preparing an alloy foil having a first component phase; (2) preparing an alloy foil having both a first component phase and a second component phase; (3) dealloying treatment; and (4) reduction annealing treatment.
[0064] By performing recrystallization annealing treatment on the alloy foil after cold rolling, an alloy foil having a first component phase and good plastic processing ability can be obtained, and the grains in the alloy foil are mainly equiaxed grains.
[0065] By adopting the phase separation heat treatment with a lowered temperature, an alloy foil having both the first component phase and the second component phase can be obtained, thereby making the dealloyed porous metal structure self-supporting.
[0066] After dealloying, porous metal structures are prone to intergranular corrosion cracks. This is because there is a certain atomic diffusion phenomenon in the cooling process after recrystallization annealing. The relatively active metal atoms in the alloy are easily enriched at the grain boundaries, while the relatively inactive metal atoms are easily enriched on both sides of the grain boundaries. Dealloying is a process of removing at least part of the relatively active metal components in the alloy foil by free corrosion or electrochemical corrosion to prepare a porous metal structure. During dealloying, the relatively active metal components are corroded first, while the uncorroded components have poor diffusion ability, which easily leads to intergranular corrosion cracks. In addition, the diffusion power of metal atoms on the alloy surface is relatively strong, so a relatively uniform pore structure can be formed on the surface through diffusion. However, due to the lower surface energy inside the alloy, the diffusion power of metal atoms is relatively weak. Therefore, after intergranular corrosion occurs after dealloying treatment, the metal atoms at the grain boundaries inside the alloy tend to remain in their original positions. At this time, the cracks left by the dealloying treatment cannot be filled, and the prepared porous metal structure has a large number of intergranular corrosion cracks. At the same time, the toughness of the prepared porous metal structure is still very poor, and large cracks are prone to occur after bending.
[0067] The reduction annealing treatment can reduce the metal oxide on the surface of the porous foil obtained by the dealloying treatment to a metal element with better diffusion ability, and can repair the intergranular corrosion cracks formed by the dealloying treatment by causing the metal atoms near the grain boundaries (mainly relatively inactive metal atoms, and can also include relatively active metal atoms that have not been completely corroded) to diffuse under heat, thereby making the prepared porous metal structure have better toughness.
[0068] A relatively large cooling rate is used in the first cooling process after the recrystallization annealing treatment. This is because the recrystallization annealing treatment is a high-temperature heat treatment, and there is still a certain atomic diffusion phenomenon in the cooling process after the high-temperature heat treatment. The relatively active metal atoms in the alloy are easily enriched at the grain boundaries, while the relatively inactive metal atoms are easily enriched on both sides of the grain boundaries, which will affect the effects of the subsequent dealloying treatment and reduction annealing treatment. After the recrystallization annealing treatment, the use of a rapid cooling process can quickly reduce the internal temperature of the alloy foil to a lower temperature and shorten the cooling time, thereby avoiding the formation of more serious element segregation problems at the grain boundaries as much as possible, and is also conducive to the diffusion of metal atoms near the grain boundaries during the subsequent reduction annealing treatment, so that the grain boundary corrosion cracks can be better repaired, and the prepared porous metal structure can also have better toughness.
[0069] The second cooling process after the phase separation heat treatment uses a relatively small cooling rate. This is because the alloy after phase separation has interphase stress between the first component phase and the second component phase. The use of a slow cooling process can reduce the interphase stress, which is conducive to the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing treatment, thereby better repairing the grain boundary corrosion cracks and making the prepared porous metal structure have better toughness.
[0070] Therefore, the preparation method provided in the embodiment of the present application can partially or even completely repair the intergranular corrosion cracks formed by the dealloying treatment, and can also make the prepared porous metal structure have better strength and toughness.
[0071] In some embodiments, the cold-rolled alloy foil can be commercially available, or can be obtained according to a preparation process known in the art, for example, through processes such as melting, cutting, annealing, and cold rolling.
[0072] In some embodiments, the average cooling rate of the first cooling treatment may be greater than or equal to 100°C / min, and may be greater than or equal to 200°C / min. This is beneficial to reducing the element segregation problem at the grain boundary, and is also beneficial for the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing treatment, so that the grain boundary corrosion cracks can be better repaired, and the prepared porous metal structure can also have better toughness.
[0073] In some embodiments, the first cooling process can be a water cooling process. This is beneficial to reduce the element segregation problem at the grain boundary, and is also beneficial to the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing treatment, so that the grain boundary corrosion cracks can be better repaired, and the prepared porous metal structure can also have better toughness. The water cooling process refers to a process in which the alloy foil is taken out from a high temperature state and then immersed in water for rapid cooling. Optionally, the temperature of the water used can be 20°C-30°C.
[0074] In some embodiments, the first temperature reduction treatment can cool the temperature of the alloy foil to below 50° C. This can reduce the risk of surface oxidation of the alloy foil during the process of transferring the alloy foil out of the furnace.
[0075] In some embodiments, the average cooling rate of the second cooling treatment may be less than or equal to 2°C / min. This is beneficial to reducing the interphase stress between the first component phase and the second component phase in the phase-separated alloy, and is beneficial to the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing treatment, so that the grain boundary corrosion cracks can be better repaired, and the prepared porous metal structure can also have better toughness.
[0076] In some embodiments, the second cooling process can be a furnace cooling process. This is beneficial to reducing the interphase stress between the first component phase and the second component phase in the phase-separated alloy, and is beneficial to the diffusion of metal atoms near the grain boundary during the subsequent reduction annealing treatment, so that the grain boundary corrosion cracks can be better repaired, and the prepared porous metal structure can also have better toughness. The furnace cooling process refers to a process in which the alloy foil is not taken out of the furnace body in a high-temperature state, but is slowly cooled naturally from a high-temperature state together with the furnace body.
[0077] In some embodiments, the second temperature reduction treatment can cool the temperature of the alloy foil to below 50° C. This can reduce the risk of surface oxidation of the alloy foil during the process of transferring the alloy foil out of the furnace.
[0078] In some embodiments, the recrystallization annealing process may be performed in a muffle furnace.
[0079] In some embodiments, before the recrystallization treatment, some anti-oxidation materials may be coated on the surface of the alloy foil to reduce the surface oxidation problem. For example, the anti-oxidation material may be made of a high-purity silicate solution, added with ultrafine inorganic metal oxides and finely processed.
[0080] In some embodiments, the phase separation heat treatment may adopt a programmed heating process, which includes a temperature rise section, a temperature holding section, and a temperature drop section.
[0081] In some embodiments, the phase separation heat treatment may be performed under the protection of an inert gas. Optionally, the inert gas may include one or more of nitrogen, argon, and helium.
[0082] In some embodiments, the phase separation heat treatment may be performed in a tube furnace. Optionally, the heating rate of the tube furnace may be 2°C / min-10°C / min, and may be 5°C / min-10°C / min.
[0083] The reduction annealing treatment can reduce the metal oxide on the surface of the porous foil obtained by the dealloying treatment to a metal element with better diffusion ability. In some embodiments, the reducing gas of the reduction annealing treatment may include ammonia or a mixture of hydrogen and an inert gas. The inert gas may include one or more of nitrogen, argon, and helium.
[0084] Optionally, the reducing gas of the reduction annealing treatment includes a mixture of hydrogen and an inert gas, and the volume fraction of hydrogen in the reducing gas may be greater than or equal to 2%, and more preferably 2%-10%. This can not only reduce the metal oxide on the surface of the porous foil obtained by the dealloying treatment to a metal element with better diffusion ability, but also ensure the safety of the operation.
[0085] Optionally, the flow rate of the reducing gas in the reducing annealing treatment may be 100 SCCM-2000 SCCM.
[0086] The reduction annealing treatment can adopt a program heating process, which includes a temperature rise section, a temperature holding section and a temperature drop section.
[0087] In some embodiments, the reduction annealing treatment may be performed in a tube furnace. Optionally, the heating rate of the tube furnace may be 2° C. / min-10° C. / min, or may be 5° C. / min-10° C. / min.
[0088] In some embodiments, the average cooling rate of the third cooling treatment may be less than or equal to 2° C. / min. The use of a slow cooling process can reduce the stress of the porous metal structure and make it less likely to curl.
[0089] In some embodiments, the third temperature reduction process may be a furnace cooling process, which refers to a process in which the porous metal structure is not taken out of the furnace body at a high temperature, but is naturally cooled slowly from a high temperature state together with the furnace body.
[0090] In some embodiments, the third cooling treatment can cool the temperature of the porous metal structure to below 50° C. This can reduce the risk of surface oxidation of the porous metal structure during the process of transferring the porous metal structure out of the furnace.
[0091] In the present application, average cooling rate = (temperature before cooling - temperature after cooling) / total cooling time.
[0092] In some embodiments, the process of dealloying the alloy foil having the first component phase and the second component phase may include a free corrosion dealloying process and an electrochemical corrosion dealloying process.
[0093] Both the free corrosion dealloying process and the electrochemical corrosion dealloying process can adopt the technology known in the art. The washing process after dealloying can include water washing and alcohol washing. Water washing can reduce the metal ion content in the porous metal structure, and alcohol washing can reduce the moisture in the pores of the porous metal structure.
[0094] Deionized water may be used for washing, and the number of washing times may be 1 to 6 times, which is not limited in the present embodiment.
[0095] The alcohol washing may be performed with anhydrous ethanol, and the number of alcohol washings may be 1 to 6 times, which is not limited in the present embodiment.
[0096] The drying process after the washing process can be carried out in a vacuum drying oven, and the drying temperature can be 25° C.-50° C., thereby reducing metal oxidation.
[0097] The etching solution used in the free-etching dealloying process may include an acidic aqueous solution, such as hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, and the like.
[0098] The etching solution used in the electrochemical etching dealloying process may include an acidic (such as hydrochloric acid, sulfuric acid, phosphoric acid, acetic acid, etc.) aqueous solution, a neutral salt (such as sodium chloride, etc.) aqueous solution, or a mixed aqueous solution of the above components.
[0099] In some embodiments, the alloy foil may be a copper alloy foil, which may include a Cu element and a non-Cu metal element, wherein the standard electrode potential of the non-Cu metal element is lower than the standard electrode potential of the Cu element, that is, the activity of the non-Cu metal element is higher than that of the Cu element. Optionally, the non-Cu metal element may include one or more of Mn, Zn, Ni, Al, and Fe.
[0100] The content of Cu element and non-Cu metal element is not specifically limited. In some embodiments, the atomic content of non-Cu metal element in copper alloy foil can be 60 at.% or more, and can be 65 at.%-85 at.%, 65 at.%-80 at.%. Thus, the prepared porous copper structure can be self-supporting, and it is also beneficial for the porous copper structure to be used in the negative electrode of the battery.
[0101] In some embodiments, the copper alloy foil may further include a small amount of non-metallic element impurities, such as C, Si, etc.
[0102] In some embodiments, the first component phase may include a γ phase. Taking a Mn-Cu alloy foil as an example, the first component phase may include a γ phase Mn-Cu alloy.
[0103] In some embodiments, the second component phase may include an α phase. Taking a Mn-Cu alloy foil as an example, the second component phase may include an α phase Mn.
[0104] In some embodiments, the temperature of the recrystallization annealing treatment can be 720°C-850°C, for example, it can be 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, or a range consisting of any of the above values, and can be optionally 760°C-820°C.
[0105] In some embodiments, the holding time at the recrystallization annealing treatment temperature can be 10 min-60 min, for example, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, or a range consisting of any of the above values, and can be selected from 15 min to 45 min.
[0106] By adjusting the temperature of the recrystallization annealing treatment and / or within the above range, it is beneficial to obtain an alloy foil having a first component phase with good plastic processing ability, and it is also beneficial to precipitate the second component phase during the phase separation heat treatment.
[0107] In some embodiments, the temperature of the phase separation heat treatment can be 620℃-700℃, for example, it can be 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, or a range consisting of any of the above values, and can be optionally 640℃-680℃.
[0108] In some embodiments, the holding time at the phase separation heat treatment temperature can be 60 min-360 min, for example, 60 min, 90 min, 120 min, 150 min, 180 min, 210 min, 240 min, 270 min, 300 min, 330 min, 360 min, or a range consisting of any of the above values.
[0109] By adjusting the temperature of the phase separation heat treatment and / or within the above range, it is beneficial to precipitate the second component phase during the phase separation heat treatment, and it is also beneficial to obtain a micron-level porous metal structure after the subsequent reduction annealing treatment.
[0110] In some embodiments, the temperature of the reduction annealing treatment can be 700°C-900°C, for example, it can be 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, or a range consisting of any of the above values, which can be selected from 720°C-900°C, 750°C-880°C, or 750°C-850°C.
[0111] In some embodiments, the holding time at the reduction annealing treatment temperature can be 30min-120min, for example, 30min, 35min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, or a range consisting of any of the above values, which can be selected from 35min-100min, 35min-80min, 35min-70min.
[0112] By adjusting the temperature and / or time of the reduction annealing treatment within the above range, it is beneficial for the metal atoms to diffuse and move due to heat, so as to better repair the intergranular corrosion cracks formed by the dealloying treatment; it can also make the prepared porous metal structure self-supporting and avoid the problem of structural collapse; it can also make the prepared porous metal structure have better toughness.
[0113] The present application also provides a porous metal structure prepared by the above preparation method, which has fewer intergranular corrosion cracks and better strength and toughness. Optionally, the porous metal structure has no intergranular corrosion cracks.
[0114] In some embodiments, the porous metal structure is a porous copper structure.
[0115] In some embodiments, the pores of the porous metal structure are mostly in the micrometer range.
[0116] Example
[0117] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0118] Example 1
[0119] (1) Preparation of α / γ dual-phase Mn-Cu alloy precursor
[0120] Pure copper (purity ≥ 99.9%) and pure manganese (purity ≥ 99.9%) raw materials are provided, and a Mn-Cu alloy is prepared by vacuum induction melting, wherein the atomic content of Mn in the Mn-Cu alloy is 75 at.%, and the atomic content of Cu is 25 at.%. The Mn-Cu alloy prepared by vacuum induction melting is cut, and then subjected to homogenization annealing treatment, multiple cold rolling and other processes to obtain a Mn-Cu alloy foil with a thickness of about 250 μm.
[0121] The Mn-Cu alloy foil is placed in a muffle furnace and recrystallized at 800°C for 20 minutes to obtain a γ single-phase Mn-Cu alloy. The γ single-phase Mn-Cu alloy foil is taken out and immediately cooled to below 50°C (i.e., the first cooling process), then washed and dried with anhydrous ethanol, and then placed in a tubular furnace for phase separation heat treatment. Before heating, the tube of the tubular furnace is vented with nitrogen to remove oxygen in the furnace tube. After the exhaust treatment, the tubular furnace is heated to 660°C at 5°C / min under the protection of a nitrogen atmosphere for phase separation heat treatment, and the insulation time is 60 minutes. After the end, it is cooled to below 50°C with the furnace (i.e., the second cooling process) to obtain an α / γ dual-phase Mn-Cu alloy precursor.
[0122] (2) Preparation of porous copper intermediates by dealloying
[0123] The α / γ dual-phase Mn-Cu alloy precursor prepared above was cut into 30mm*30mm samples, and placed in an excess of 1mol / L hydrochloric acid aqueous solution, and free corrosion was carried out at 70°C for dealloying treatment; when no obvious bubbles escaped from the hydrochloric acid aqueous solution, the sample was taken out and soaked in 200mL of deionized water for 30min to remove residual hydrochloric acid and manganese-containing impurities in the sample, and then soaked in 100mL of anhydrous ethanol for 30min to remove residual moisture in the sample, and finally vacuum dried at 25°C for 2h to obtain a porous copper intermediate with intergranular corrosion cracks.
[0124] (3) Preparation of porous copper structure by reduction annealing
[0125] The porous copper intermediate prepared as above is placed in a corundum boat, and then placed in a tubular furnace for reduction annealing. Before heating, the furnace tube of the tubular furnace is exhausted with a 5% hydrogen-argon mixture (hydrogen accounts for 5% by volume) to remove oxygen in the furnace tube. After the exhaust treatment is completed, a 5% hydrogen-argon mixture (hydrogen accounts for 5% by volume) is used to fill the tubular furnace with reducing gas and the gas flow rate is adjusted to 500SCCM. The tubular furnace is heated to 800°C at 5°C / min for reduction annealing treatment, and the insulation time is 40 minutes. After the end, the furnace is cooled to below 50°C (i.e., the third cooling treatment process) to obtain a porous copper structure.
[0126] Example 2
[0127] The preparation process of the porous copper structure is the same as that of Example 1, except that the holding time of the phase separation heat treatment is 210 min when preparing the α / γ dual-phase Mn-Cu alloy precursor.
[0128] Example 3
[0129] The preparation process of the porous copper structure is the same as that of Example 1, except that the holding time of the phase separation heat treatment is 360 min when preparing the α / γ dual-phase Mn-Cu alloy precursor.
[0130] Example 4
[0131] The preparation process of the porous copper structure is the same as that of Example 3, except that the temperature of the phase separation heat treatment is 620° C. when preparing the α / γ dual-phase Mn—Cu alloy precursor.
[0132] Example 5
[0133] The preparation process of the porous copper structure is the same as that of Example 3, except that the temperature of the phase separation heat treatment is 700° C. when preparing the α / γ dual-phase Mn—Cu alloy precursor.
[0134] Example 6
[0135] The preparation process of the porous copper structure is the same as that of Example 2, except that the temperature of the reduction annealing treatment is 700° C.
[0136] Example 7
[0137] The preparation process of the porous copper structure is the same as that of Example 2, except that the temperature of the reduction annealing treatment is 900° C.
[0138] Example 8
[0139] The preparation process of the porous copper structure is the same as that of Example 2, except that the reduction annealing treatment time is 80 min.
[0140] Example 9
[0141] The preparation process of the porous copper structure is the same as that of Example 2, except that the reduction annealing treatment time is 120 min.
[0142] Example 10
[0143] The preparation process of the porous copper structure is the same as that of Example 2, except that the temperature of the recrystallization annealing treatment is 720° C. and the holding time is 60 min when preparing the α / γ dual-phase Mn—Cu alloy precursor.
[0144] Embodiment 11
[0145] The preparation process of the porous copper structure is the same as that of Example 2, except that the temperature of the recrystallization annealing treatment is 850° C. and the holding time is 10 min when preparing the α / γ dual-phase Mn—Cu alloy precursor.
[0146] Comparative Example 1
[0147] The preparation process of the porous copper structure is the same as that of Example 1 except that the process of preparing the α / γ dual-phase Mn—Cu alloy precursor is different.
[0148] (1) Preparation of α / γ dual-phase Mn-Cu alloy precursor
[0149] Pure copper (purity ≥ 99.9%) and pure manganese (purity ≥ 99.9%) raw materials are provided, and a Mn-Cu alloy is prepared by vacuum induction melting, wherein the atomic content of Mn in the Mn-Cu alloy is 75 at.%, and the atomic content of Cu is 25 at.%. The Mn-Cu alloy prepared by vacuum induction melting is cut, and then subjected to homogenization annealing treatment, multiple cold rolling and other processes to obtain a Mn-Cu alloy foil with a thickness of about 250 μm.
[0150] The Mn-Cu alloy foil is placed in a muffle furnace at 800°C for recrystallization annealing treatment, and the holding time is 20 minutes. After the end, it is cooled to below 50°C with the furnace (i.e., the first cooling treatment process) to obtain a γ single-phase Mn-Cu alloy foil. The γ single-phase Mn-Cu alloy foil is taken out and placed in a tubular furnace for phase separation heat treatment. Before heating, the furnace tube of the tubular furnace is exhausted with nitrogen to remove oxygen in the furnace tube. After the exhaust treatment is completed, the tubular furnace is heated to 660°C at 5°C / min under the protection of a nitrogen atmosphere for phase separation heat treatment, and the holding time is 210 minutes. After the end, it is cooled to below 50°C with the furnace (i.e., the second cooling treatment process) to obtain an α / γ dual-phase Mn-Cu alloy precursor.
[0151] Comparative Example 2
[0152] The preparation process of the porous copper structure is the same as that of Example 1 except that the process of preparing the α / γ dual-phase Mn—Cu alloy precursor is different.
[0153] (1) Preparation of α / γ dual-phase Mn-Cu alloy precursor
[0154] Pure copper (purity ≥ 99.9%) and pure manganese (purity ≥ 99.9%) raw materials are provided, and a Mn-Cu alloy is prepared by vacuum induction melting, wherein the atomic content of Mn in the Mn-Cu alloy is 75 at.%, and the atomic content of Cu is 25 at.%. The Mn-Cu alloy prepared by vacuum induction melting is cut, and then subjected to homogenization annealing treatment, multiple cold rolling and other processes to obtain a Mn-Cu alloy foil with a thickness of about 250 μm.
[0155] The Mn-Cu alloy foil is placed in a muffle furnace and recrystallized at 800°C for 20 minutes to obtain a γ single-phase Mn-Cu alloy. The γ single-phase Mn-Cu alloy foil is taken out and immediately cooled to below 50°C (i.e., the first cooling process), then washed and dried with anhydrous ethanol, and then placed in a tube furnace for phase separation heat treatment. Before heating, the tube of the tube furnace is exhausted with nitrogen to remove oxygen in the tube. After the exhaust treatment, the tube furnace is heated to 660°C at 5°C / min under the protection of a nitrogen atmosphere for phase separation heat treatment, and the insulation time is 210 minutes. After the end, the alloy foil is taken out and immediately cooled to below 50°C (i.e., the second cooling process), and then washed and dried with anhydrous ethanol to obtain an α / γ dual-phase Mn-Cu alloy precursor.
[0156] Comparative Example 3
[0157] The preparation process of the porous copper structure is the same as that of Example 1, except that the reduction annealing treatment is not performed (ie, step 3 is not performed).
[0158] Comparative Example 4
[0159] The preparation process of the porous copper structure is the same as that of Comparative Example 2, except that the reduction annealing treatment is not performed (ie, step 3 is not performed).
[0160] Comparative Example 5
[0161] Pure copper (purity ≥ 99.9%) and pure manganese (purity ≥ 99.9%) raw materials are provided, and a Mn-Cu alloy is prepared by vacuum induction melting, wherein the atomic content of Mn in the Mn-Cu alloy is 75 at.%, and the atomic content of Cu is 25 at.%. The Mn-Cu alloy prepared by vacuum induction melting is cut, and then subjected to homogenization annealing treatment, multiple cold rolling and other processes to obtain a Mn-Cu alloy foil with a thickness of about 250 μm.
[0162] The Mn-Cu alloy foil was placed in a muffle furnace at 800°C for recrystallization annealing treatment with a holding time of 20 minutes. After the annealing, the alloy foil was taken out and immediately water-cooled to below 50°C (i.e., the first cooling treatment process), and then washed with anhydrous ethanol and dried to obtain a γ single-phase Mn-Cu alloy foil.
[0163] The γ single-phase Mn-Cu alloy precursor prepared above was cut into 30mm*30mm samples, and placed in an excess of 1mol / L hydrochloric acid aqueous solution, and free corrosion was carried out at 70°C for dealloying treatment; when no obvious bubbles escaped from the hydrochloric acid aqueous solution, the sample was taken out and soaked in 200mL of deionized water for 30min to remove residual hydrochloric acid and manganese-containing impurities in the sample, and then soaked in 100mL of anhydrous ethanol for 30min to remove residual moisture in the sample, and finally vacuum dried at 25°C for 2h to obtain a fragile porous copper structure.
[0164] Comparative Example 6
[0165] Pure copper (purity ≥ 99.9%) and pure manganese (purity ≥ 99.9%) raw materials are provided, and a Mn-Cu alloy is prepared by vacuum induction melting, wherein the atomic content of Mn in the Mn-Cu alloy is 75 at.%, and the atomic content of Cu is 25 at.%. The Mn-Cu alloy prepared by vacuum induction melting is cut, and then subjected to homogenization annealing treatment, multiple cold rolling and other processes to obtain a Mn-Cu alloy foil with a thickness of about 250 μm.
[0166] The Mn-Cu alloy foil was placed in a muffle furnace at 800°C for recrystallization annealing treatment with a holding time of 20 minutes. After the annealing, the foil was cooled to below 50°C (i.e., the first cooling treatment process) to obtain a γ single-phase Mn-Cu alloy foil.
[0167] The γ single-phase Mn-Cu alloy precursor prepared above was cut into 30mm*30mm samples, and placed in an excess of 1mol / L hydrochloric acid aqueous solution, and free corrosion was carried out at 70°C for dealloying treatment; when no obvious bubbles escaped from the hydrochloric acid aqueous solution, the sample was taken out and soaked in 200mL of deionized water for 30min to remove residual hydrochloric acid and manganese-containing impurities in the sample, and then soaked in 100mL of anhydrous ethanol for 30min to remove residual moisture in the sample, and finally vacuum dried at 25°C for 2h to obtain a fragile porous copper structure.
[0168] The cross-sectional SEM images of the porous copper intermediate obtained by dealloying treatment and the porous copper structure obtained by reduction annealing treatment were scanned by scanning electron microscope, and the degree of repair of grain boundary corrosion cracks was determined by counting the number of grains with grain boundary corrosion cracks. The test instrument is a Phenom XL G2 desktop scanning electron microscope with a magnification of 5000 times. In order to test the accuracy, SEM images can be obtained from the middle area of the porous copper intermediate and the porous copper structure in the thickness direction. The selected area size is about 105μm×65μm.
[0169] The porous copper structure prepared above is slowly bent along the center line, and the bending speed is less than or equal to 0.02rad / s. When the dihedral angle formed by the two faces after bending is 120°, observe whether the center line has cracks, so as to judge the bending performance of the porous copper structure. If no cracks are generated at the center line position after bending or the width of the cracks generated is less than 0.1mm, it is considered that the toughness of the porous copper structure is good. If the width of the cracks generated at the center line position after bending is between 0.1mm and 0.3mm, it is considered that the toughness of the porous copper structure is good. If the width of the cracks generated at the center line position after bending is greater than 0.3mm, it is considered that the toughness of the porous copper structure is poor.
[0170] The test results are shown in Table 1. In Table 1, the symbol "—" indicates that the corresponding treatment was not performed, or the corresponding test could not be performed.
[0171] Table 1
[0172]
[0173] Figure 1 A cross-sectional SEM image of the porous copper intermediate obtained by the dealloying treatment in Example 1 is shown. Figure 2 The cross-sectional SEM image of the porous copper intermediate obtained by the dealloying treatment in Example 1 is shown, and the porous copper intermediate is subjected to plasma cutting and polishing treatment. Figure 3 A cross-sectional SEM image of the porous copper structure prepared in Example 1 is shown. Figure 4 A cross-sectional SEM image of the porous copper structure prepared in Example 2 is shown. Figure 5 A cross-sectional SEM image of the porous copper structure prepared in Example 6 is shown. Figure 6 A cross-sectional SEM image of the porous copper structure prepared in Example 7 is shown.
[0174] Depend on Figures 1 to 3It can be seen that the preparation method provided in the embodiment of the present application can make the intergranular corrosion cracks of the porous copper intermediate obtained by the dealloying treatment be well repaired, and the porous metal structure prepared by the preparation method provided in the embodiment of the present application can be self-supporting, thus having good strength. Combined with the test results in Table 1, it can also be seen that the porous metal structure prepared by the preparation method provided in the embodiment of the present application also has good toughness.
[0175] Figure 7 A cross-sectional SEM image of the porous copper intermediate obtained by dealloying treatment in Comparative Example 1 is shown. Figure 8 A cross-sectional SEM image of the porous copper intermediate obtained by the dealloying treatment in Comparative Example 1 is shown, and the porous copper intermediate is subjected to plasma cutting and polishing treatment. Fig. 9 A cross-sectional SEM image of the porous copper structure prepared in Comparative Example 1 is shown.
[0176] Depend on Figures 7 to 9 It can be seen that the intergranular corrosion cracks of the porous copper intermediate obtained by the dealloying treatment in Comparative Example 1 have not been effectively repaired. Combined with the test results in Table 1, it can also be seen that the toughness of the porous copper structure prepared in Comparative Example 1 is still poor, and large cracks will be generated when bent to 120°. This is because the first cooling process after the recrystallization annealing treatment adopts a furnace cooling process, and the recrystallization annealing treatment is a high-temperature heat treatment. There is a certain atomic diffusion phenomenon in the cooling process after the high-temperature heat treatment. The Mn atoms in the alloy are easily enriched at the grain boundaries, and the Cu atoms are easily enriched on both sides of the grain boundaries (i.e., a thick copper barrier is formed). The cooling rate of the furnace cooling process is very small, which greatly increases the cooling time, and serious element segregation problems will be formed at the grain boundaries, which will lead to the diffusion of metal atoms near the grain boundaries during the subsequent reduction annealing treatment. The grain boundary corrosion cracks cannot be effectively repaired, and the toughness of the prepared porous metal structure will also be reduced.
[0177] Depend on Figure 4 , Figure 5 and Figure 6 It can also be seen that the time of the reduction annealing treatment remains unchanged. By adjusting the temperature of the reduction annealing treatment, it is beneficial for the metal atoms to diffuse and move due to heat, thereby better repairing the intergranular corrosion cracks formed by the dealloying treatment. Combined with the test results in Table 1, it can also be seen that by adjusting the temperature of the reduction annealing treatment, the toughness of the prepared porous metal structure can also be improved.
[0178] Fig.10 The cross-sectional SEM image of the porous copper structure prepared in Comparative Example 2 is shown. Fig.10It can be seen that when the second cooling treatment process after the phase separation heat treatment adopts the water cooling process, the phase-separated alloy has interphase stress between the first component phase and the second component phase, which leads to the thermal diffusion of metal atoms being hindered during the subsequent reduction annealing treatment. There are many intergranular corrosion cracks in the prepared porous metal structure that have not been effectively repaired. At the same time, the toughness of the prepared porous copper structure is still poor, and larger cracks will occur when bent to 120°.
[0179] Fig.11 The cross-sectional SEM image of the porous copper structure prepared in Comparative Example 5 is shown. Fig.11 It can be seen that the alloy foil after cold rolling is only subjected to recrystallization annealing treatment without phase separation heat treatment, and the porous metal structure obtained by the dealloying treatment is fragile and cannot be self-supporting.
[0180] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a porous metal structure, characterized in that: The steps include: Provide cold rolled alloy foil; The alloy foil is subjected to a recrystallization annealing treatment, and then subjected to a first cooling treatment to obtain an alloy foil having a first component phase; The alloy foil having the first component phase is subjected to a phase separation heat treatment, and then subjected to a second cooling treatment to precipitate the second component phase and obtain an alloy foil having both the first component phase and the second component phase, wherein the temperature of the phase separation heat treatment is lower than the temperature of the recrystallization annealing treatment, and the average cooling rate of the second cooling treatment is lower than the average cooling rate of the first cooling treatment; The alloy foil having the first component phase and the second component phase is dealloyed, then subjected to reduction annealing in a reducing gas atmosphere, and then subjected to a third cooling treatment to obtain a porous metal structure.
2. The preparation method according to claim 1, characterized in that: The average cooling rate of the first cooling treatment is greater than or equal to 100°C / min, and may be greater than or equal to 200°C / min; and / or, The average cooling rate of the second cooling treatment is less than or equal to 2°C / min.
3. The preparation method according to any one of claims 1 to 2, characterized in that: The first cooling process is a water cooling process; and / or, The second temperature reduction treatment process is a furnace cooling process.
4. The preparation method according to any one of claims 1 to 3, characterized in that The first cooling treatment is cooling to below 50°C; and / or, The second cooling treatment is cooling to below 50°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The recrystallization annealing treatment is performed in a muffle furnace; and / or, The phase separation heat treatment is carried out in a tubular furnace. Optionally, the heating rate of the tubular furnace is 2°C / min-10°C / min, and can be optionally 5°C / min-10°C / min.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The reducing gas of the reduction annealing treatment includes a mixture of ammonia or hydrogen and an inert gas; and / or, The flow rate of the reducing gas in the reduction annealing treatment is 100 SCCM-2000 SCCM.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The reduction annealing treatment is carried out in a tube furnace, and optionally, the heating rate of the tube furnace is 2°C / min-10°C / min, and optionally 5°C / min-10°C / min; and / or, The average cooling rate of the third cooling treatment is less than or equal to 2°C / min. Optionally, the third cooling treatment process is a furnace cooling process; and / or, The third cooling treatment is cooling to below 50°C.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The alloy foil is a copper alloy foil, which includes a Cu element and a non-Cu metal element. The standard electrode potential of the non-Cu metal element is smaller than the standard electrode potential of the Cu element. Optionally, the non-Cu metal element includes one or more of Mn, Zn, Ni, Al, and Fe.
9. The preparation method according to claim 8, characterized in that: The atomic content of the non-Cu metal element in the copper alloy foil is greater than 60 at.%, and can be selected from 65 at.% to 80 at.%.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The first component phase comprises a γ phase; and / or, The second component phase includes an alpha phase.
11. The preparation method according to any one of claims 1 to 10, characterized in that: The temperature of the recrystallization annealing treatment is 720°C-850°C; and / or, The holding time at the recrystallization annealing temperature is 10 min-60 min; and / or, The temperature of the phase separation heat treatment is 620°C-700°C; and / or, The holding time at the phase separation heat treatment temperature is 60 min-360 min; and / or, The temperature of the reduction annealing treatment is 700° C.-900° C., and can be 720° C.-900° C.; and / or, The holding time at the reduction annealing treatment temperature is 30 min-120 min.
12. The preparation method according to any one of claims 1 to 11, characterized in that: The process of dealloying the alloy foil having the first component phase and the second component phase includes a free corrosion dealloying process and an electrochemical corrosion dealloying process.
13. A porous metal structure prepared by the preparation method according to any one of claims 1 to 12, optionally, the porous metal structure is a porous copper structure.
Citation Information
Cited By
Porous metal structure and preparation method therefor
EP4682294A1